Dimensi Metrik Ketetanggaan Lokal pada Graf Hasil Operasi Korona G odot P_3 dan G odot S_4 - Alfin Nabila Taufik; Dafik Dafik; Rafiantika Megahnia Prihandini; Ridho Alfarisi (jcgant, 2020)
There are variant of the metric dimensions in graph theory, one of them is a local adjacency metric dimension. Let WV(G) with W={w_1,w_2,…,w_k}, the representation of the vertex VV(G), r_A(v|W)=(d_A(v,w_1),d_A(v,w_2),…,d_A(v,w_k)) with d_ A (v, w) = 0 if v = w , d_ A (v, w) = 1 if v adjacent to w , and d_ A (v, w) = 2 if v does not adjacent to w . If every two adjacent vertices v_1 , v_2 V (G) , r_ A (v_1 | W) ≠ r_ A (v_2 | W) , then W is the minimum cardinality of the local adjacency metric dimension. The minimum cardinality of W is called the local adjacency metric dimension number, denoted by _(A, l) (G) . In this paper, we have found the local adjacency metric dimension of corona product of special graphs, namely the L_n P_3 graph, S_n P_3 graph, C_n P_3 graph, P_n S_4 graph, and the graph L_n S_4 .